NMR Characterization of the Interactions Between Glycosaminoglycans and Proteins - Bu, Changkai; Jin, Lan (Frontiers in Molecular Biosciences, 2021)
Glycosaminoglycans (GAGs) constitute a considerable fraction of the glycoconjugates found on cellular membranes and in the extracellular matrix of virtually all mammalian tissues. The essential role of GAG-protein interactions in the regulation of physiological processes has been recognized for decades. However, the underlying molecular basis of these interactions has only emerged since 1990s. The binding specificity of GAGs is encoded in their primary structures, but ultimately depends on how their functional groups are presented to a protein in the three-dimensional space. This review focuses on the application of NMR spectroscopy on the characterization of the GAG-protein interactions. Examples of interpretation of the complex mechanism and characterization of structural motifs involved in the GAG-protein interactions are given. Selected families of GAG-binding proteins investigated using NMR are also described.